Percentile rankings and normalization of performance for youth International Weightlifting Federation world championships competitors - Gillen, Z. (International Journal of Strength and Conditioning, 2025)
The present study provided percentile rankings and comparisons based on sex and weight class for absolute and normalized Olympic Weightlifting (OW) performance for youth International Weightlifting Federation (IWF) World Championships competitors. Data from the IWF Youth World Championships from 2019, 2021, 2022, and 2023 were used. Allometric scaling normalized OW performance to body weight, and Sinclair scores were calculated based on IWF standards. Percentile rankings and sex and weight class differences were analyzed. In general, boys were stronger than girls for absolute and allometrically scaled OW performance, and Sinclair scores. Within boys and girls, absolute OW performance increased with weight class, while the middle weight classes tended to have superior performance than the lightest and heaviest weight classes when allometrically scaled. For the boys, Sinclair scores were greater for the middle weight classes compared to the lightest and heaviest weight classes. For the girls, there were no differences across weight class for Sinclair scores. The present study provides sex- and weight class-specific percentile rankings for absolute and normalized performance for youth OW competitors. These data may be valuable for assessing youth OW competitors and when considering appropriate weight classes for these competitors.